Balanced asset allocation how to profit in any economic climate - Shahidi, Alex (Wiley, 2015)
"Presenting an optimized, balance asset allocation approach to investment portfoliosManaging an investment portfolio can be rewarding and profitable, but those without experience in various economic climates can make key mistakes that can expose them to undue risk. Merrill Lynch investment consultant Alex Shahidi puts his 13 years of experience to work in this resource that helps investors maximize returns while minimizing risk with a balanced asset allocation portfolio. With Balanced Asset Allocation: How to Profit in Any Economic Climate, Shahidi shows the individual investor how to reduce risk and capably adjust to changing macroeconomic conditions. In the investment world, "conventional wisdom" is a concept that can get individual investors into trouble. Author Alex Shahidi introduces the notion of the "e-Balanced" portfolio to the investor trying to combine greater stability, increased returns, and adequate downside risk mitigation within the context of a truly well-balanced portfolio. Provides concepts and approaches developed by a top-ranked investment consultant Proposes successful hedge fund approaches used by the author to generate profits Introduces the concept of the "e-Balanced" portfolio to minimize exposure to stock fluctuations Contains information to deftly navigate volatile markets using proven macroeconomic principles For those who want to manage their personal investment portfolio but need an asset allocation primer, Balanced Asset Allocation: How to Profit in Any Economic Climate provides an in-depth treatment of the topic that can be put to use immediately"--
Includes index
Keywords: Finance, Personal; Investments; Portfolio management; Investissements; Gestion de portefeuille; BUSINESS & ECONOMICS; Finance